Human neurocysticercosis: IgE in cerebrospinal fluid Neurocisticercose humana: IgE no líquido cefalorraquiano - Carmen Silvia de Melo; Adelaide José Vaz; Paulo Mutuko Nakamura; Marcos Vinicius da Silva; Aluízio de Barros Barreto Machado (Arquivos de Neuro-Psiquiatria)
The detection of IgE is technically difficult because of its reduced concentrations in serum, and even lower concentrations in cerebrospinal fluid (CSF). In the present investigation we studied 86 CSF samples using an immunoenzymatic method with an anti-IgE-alkaline phosphatase conjugate and a fluorigenic substrate. The samples were from three groups: A) 29 patients with neurocysticercosis (NC), B) 36 patients with different neurologic disorders (neurosyphilis, neurotuberculosis, meningitis, tumors, hemorrhage) and C) 21 discharged individuals who had been hospitalized for bacterial meningitis. The results obtained were: A) 0.05 to 3.00 IU/ml (0.76±0.79), B) 0.00 to 1.50 IU/ml (0.23±0.34) and C) 0.05 to 1.25 IU/ml (0.34±0.34). The present results suggest that IgE appears to play a role in the pathogeny of NC and that efforts should be made to standardize a test for the detection of specific IgE antibodies. A detecção de IgE apresenta dificuldades técnicas pela reduzida concentração que se encontra no LCR e no soro. Utilizando método imunoenzimático com conjugado anti-IgE-fosfatase alcalina e substrato fluorigênico, foram estudadas 86 amostras de LCR de três grupos: A) 29 pacientes com NC, B) 36 pacientes com afecções neurológicas diversas (neurossífilis, neurotuberculose, meningites, tumores, hemorragias) e C) 21 indivíduos de pós-alta médica de meningites bacterianas. Os resultados obtidos foram: A) 0,05 a 3,00 Ul/ml (0,76±0,79), B) 0,00 a 1,50 Ul/ml (0,23±0,34) e C) 0,05 a 1,25 Ul/ml (0,34±0,34). Os resultados obtidos sugerem que a IgE parece ter papel na patogenia da NC e esforços devem ser feitos para padronização de teste para detecção de anticorpos IgE específicos.